Die Protokollbücher des Ordens vom Goldenen Vlies - Teil 4: Der Übergang an das Haus Habsburg (1477 bis 1480) - Dünnebeil, Sonja (Kieler Werkstücke Reihe D: Beiträge zur europäischen Geschichte des späten Mittelalters, 2016)
The record books of the Order of Golden Fleece are the main source for the history of this important order of knighthood, which has been existing from the 15th century up to the present time. The here presented 4th record book covers the activities of the Order between 1477 and 1480 with the magnificent assembly in Bruges in spring 1478 as its climax: The Habsburgs Maximilian I as new Duke of Burgundy was installed as the new sovereign of the Order, symbolizing the beginning of a new era in the crisis-shaken Duchy of Burgundy. The volume contains the edition of the complete text (in 15th century French) with detailed commentary (in German) and a calendar of short abstracts of the letters issued by the Order or addressed to it. The edition of the record book with their exact details concerning the location of the meetings, participants, agenda, resolutions, elections and ceremonies present a hitherto unstudied source of the history of Order. The book also offers an interesting view of the critical period within the history of the Duchy Burgundy, in that because it also deals with questions of identity, social control as well as of loyalty and felony.